In-plane compression of graded hierarchical honeycombs. Issue 7 (May 2022) - Wang, Yuyang; Lu, Guoxing; San Ha, Ngoc; Wang, Li
Hierarchical and graded honeycomb structures are extensively applied in many fields due to their excellent compression properties and energy absorption capacity. In the present study, the segmented graded hierarchical honeycomb structures with triangle substructures (GHT) are constructed to numerically investigate the in-plane crushing performance by the nonlinear finite element analysis code ABAQUS/Explicit. GHT exhibits the best energy absorption capacity compared to graded regular hexagonal honeycomb structures (GRH), graded hierarchical structures with Kagome substructures (GHK) and graded hierarchical structures with hexagonal substructures (GHH). The comprehensive effect of inertia and yield strength at each layer is illustrated by investigating the deformation modes under different loading speeds. The plateau stress is discussed in two ways: the overall average plateau stress corresponding to the whole structure and the segmental plateau stress corresponding to the specific layer. The relationship between overall average plateau stress, relative density and loading speed for the graded structure is established based on one-dimensional shock wave theory and compared with the uniform structure. The segmental properties of plateau stress at both impact and fixed ends are investigated in detail by combining theoretical analysis and deformation characteristics, and the results show good consistency with the simulation results at low, medium, and high loading speed conditions. Finally, the concept of cyclic graded structure is introduced, which can further optimize the energy absorption capacity and provide guidance for the design of new multifunctional structures.